ANALISIS INFORMASI PRODUK PESTISIDA PADA PLATFORME-COMMERS STUDI KASUS TOKO ANUGRAH TANI - Gilang Anugrah Ramadhan (PT. ZIVANA CENDEKIAWAN BANGSA, 2026)
The development of digital technology and the increasing use of e-commerce platforms have significantly transformed the distribution and marketing of agricultural products, including pesticides. Through e-commerce, farmers can access various pesticide options more quickly, easily, and efficiently. However, this convenience must be supported by complete, accurate, and standardized product information to ensure safe and effective pesticide use. This study aims to analyze the completeness of information for five pesticide products sold by Anugrah Tani Store on an e-commerce platform. The analysis parameters include product name, price, benefits, target weeds, application dosage, mode of action, and conformity to pesticide information standards recommended by the Ministry of Agriculture. The findings show that although basic information such as usage and dosage is provided, several essential components—such as active ingredients, toxicity levels, safety precautions, environmental risks, and recommendations for personal protective equipment—remain incomplete. The absence of these critical elements may affect consumer trust and increase the risk of misuse in the field. Therefore, enhancing the completeness and clarity of product descriptions is necessary to support more accurate purchasing decisions and safer pesticide application.